Efficacy of major nutrients in rice production (Bangladesh Journal of Agricultural Research, 2009)
Nutrients efficacy means increased rice yield upon soil fertilization. Purposefully a particular nutrient stress was created in soil through missing element technique from complete treatment (NPKSZn) and its reserve management (addition of omitted nutrient) effect in increasing yield was considered as a measuring stick of nutrients efficacy. The omission of all NPKSZn fertilizers from complete treatment (NPKSZn) drastically decreased yield than continuously fertilized complete treatment. Similar extent of' yield increase was observed when all NPKSZn fertilizer was applied in absolute control plot indicating that every soil needs complete addition of NPKSZn fertilizers irrespective of seasons whether the plot was continuously fertilized or not. The amount of yield increase obtained upon a missing element fertilization nearly equivalent amount of yield loss as aloofness of that particular nutrient as compared to complete fertilization. It means lhc efficacy of each essential nutrient might increase yield in a similar manner depending on their magnitude of deficiency level in the soil. Continuous application of N @ 120 kg/ha in boro and 80 kg/ha in T.aman with PKSZn @ 25-33-20-05 kg/ha per season improve total soil N, S and Zn. But exchangeable K decreased compared to initial soil status. In case of P fertilization, this rate maintained the initial soil P level. However, available Zn was found well above critical level even after 45th crop as because of high initial soil available Zn level. Key Words: Nutrient efficacy, rice yield, soil fertilization. doi: 10.3329/bjar.v33i4.2308 Bangladesh J. Agril. Res. 33(4) : 639-645, December 2008